Adult Gross Motor Learning and Sleep: Is There a Mutual Benefit? - Monica Christova; Hannes Aftenberger; Raffaele Nardone; Eugen Gallasch (Neural Plasticity)
Posttraining consolidation, also known as offline learning, refers to neuroplastic processes and systemic reorganization by which newly acquired skills are converted from an initially transient state into a more permanent state. An extensive amount of research on cognitive and fine motor tasks has shown that sleep is able to enhance these processes, resulting in more stable declarative and procedural memory traces. On the other hand, limited evidence exists concerning the relationship between sleep and learning of gross motor skills. We are particularly interested in this relationship with the learning of gross motor skills in adulthood, such as in the case of sports, performing arts, devised experimental tasks, and rehabilitation practice. Thus, the present review focuses on sleep and gross motor learning (GML) in adults. The literature on the impact of sleep on GML, the consequences of sleep deprivation, and the influence of GML on sleep architecture were evaluated for this review. While sleep has proven to be beneficial for most gross motor tasks, sleep deprivation in turn has not always resulted in performance decay. Furthermore, correlations between motor performance and sleep parameters have been found. These results are of potential importance for integrating sleep in physiotherapeutic interventions, especially for patients with impaired gross motor functions.